INSTRUCTIONAL LEADERSHIP PROFILE OF JUNIOR HIGH SCHOOL’S PRINCIPAL (A Case Study of Junior High School in Malang) - Gunawan, Imam (Faculty of Education Universitas Negeri Malang, 2017)
This study aims to determine the profile of instructional leadership shown by the Principal of Junior High School, Malang City. The experiment was conducted with a qualitative approach. The technique of collecting data used interview, observation, and documentation. Data was analyzed using an interactive model as proposed by Miles and Huberman. The results showed the profile of instructional leadership principals were: (1) the action according to the vision and mission of the school; (2) developing the curriculum according to the vision, mission, and objectives of the school; (3) develop schools towards learning organization; (4) work hard to achieve the success of the school as a learning organization; (5) creating a culture and school climate conducive to learning and innovative; and (6) manage learners in order to develop its capacity. Keywords: instructional leadership, principal, junior high school